The Influence Of Work Engagement And Organizational Culture On Employee Performance At The Regional Secretariat Of Lebong District - Reni Doyun Putri; Ida Ayu Made E.G; Wagini Wagini (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the effect of work engagement and organizational culture on employee performance at the Regional Secretariat of Lebong Regency. The sample in this study was 79 employees at the Regional Secretariat of Lebong Regency who had become civil servants. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing. The results of the regression analysis showed Y = 13.198 + 0.288X1 + 0.416 X2, this illustrates a positive regression direction, meaning that there is a positive influence between X1 (work engagement) and X2 (organizational culture) on performance (Y). It means that if the work engagement and organizational culture variables increase, performance will increase. The value of the coefficient of determination is 0.376. This means that X1 (work engagement) and X2 (organizational culture) have an effect on performance (Y) of 37.6% while the remaining 62.4% is influenced by other variables not examined in this study. The results of the t test at a significance level of 0.05 explain that partially the work engagement and organizational culture variables have a significant influence on employee performance variables at the Regional Secretariat Office of Lebong Regency. The results of the F test at a significance level of 0.05 explain that the variable work engagement and organizational culture have a significant simultaneous influence on employee performance at the Regional Secretariat Office of Lebong Regency.